Short Duration Gamma-Ray Bursts and Their Outflows in Light of GW170817 - Lazzati, Davide (Frontiers in Astronomy and Space Sciences, 2020)
The detection of GW170817, it's extensive multi-wavelength follow-up campaign, and the large amount of theoretical development and interpretation that followed, have resulted in a significant step forward in the understanding of the binary neutron star merger phenomenon as a whole. One of its aspects is seeing the merger as a progenitor of short gamma-ray bursts (SGRB), which will be the subject of this review. On the one hand, GW170817 observations have confirmed some theoretical expectations, exemplified by the confirmation that binary neutron star mergers are the progenitors of SGRBs. In addition, the multimessenger nature of GW170817 has allowed for gathering of unprecedented data, such as the trigger time of the merger, the delay with which the gamma-ray photons are detected, and the brightening afterglow of an off-axis event. All together, the incomparable richness of the data from GW170817 has allowed us to paint a fairly detailed picture of at least one SGRB. I will detail what we learned, what new questions have arisen, and the perspectives for answering them when a sample of GW170817-comparable events have been studied.